IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Nur Nabila Farhana Kamarrudin - Kamarrudin, Nur Nabila Farhana (2015)
Article on: Article 1 - “Audio-visual interactions in environment assessment” Article 2 - “Immersive virtual reality and environmental noise assessment: An innovative audio–visual approach”